PERANCANGAN ARSITEKTUR ENTERPRISE PADA BADAN PENDAPATAN DAERAH PROVINSI JAWA BARAT DI BIDANG PENGENDALIAN DAN EVALUASI PENDAPATAN MENGGUNAKAN TOGAF - Syaffa, Naura Imanda; Fajrillah, Asti Amalia Nur; Hanafi, Ridha (Jurnal Teknologi Informasi dan Pendidikan, 2023)
The use of information systems in electronic-based government systems (SPBE) has become the main focus in an attempt to enhance the quality of public services in Indonesia. Bapenda West Java Province is one of the organizations responsible for managing regional revenue and providing services to the public. This research aims to design an enterprise architecture in the Revenue Control and Evaluation Division of the West Java Provincial Revenue Agency using TOGAF. This research was conducted as an attempt to enhance the quality of public services through the implementation of information technology in the Electronic-Based Government System (SPBE). Currently, the evaluation of SPBE in West Java Province shows a "Good" predicate but still requires improvement. The method applied is the use of qualitative methods by conducting interview sessions and evaluations of stakeholders. The data collected includes guidelines for regulations applied in designing SPBE architecture, information about the West Java Provincial Revenue Agency, and evaluations of business processes and available data. This research findings suggest that there are several adjustments that need to be made in the business process of the Revenue Control and Evaluation Division of Bapenda West Java Province, as well as the importance of developing service architecture, data and information, and applications. Thus, this study intended to design an enterprise architecture blueprint and IT Roadmap that can increase the value of SPBE in West Java Province.